Earth's Alfvén Wings Driven by the April 2023 Coronal Mass Ejection - Li‐Jen Chen; Daniel Gershman; Brandon Burkholder; Yuxi Chen; Menelaos Sarantos; Lan Jian; James Drake; Chuanfei Dong; Harsha Gurram; Jason Shuster; Daniel B. Graham; Olivier Le Contel; et al. (Geophysical Research Letters)
Abstract We report a rare regime of Earth's magnetosphere interaction with sub‐Alfvénic solar wind in which the windsock‐like magnetosphere transforms into one with Alfvén wings. In the magnetic cloud of a Coronal Mass Ejection (CME) on 24 April 2023, NASA's Magnetospheric Multiscale mission distinguishes the following features: (a) unshocked and accelerated low‐beta CME plasma coming directly against Earth's dayside magnetosphere; (b) dynamical wing filaments representing new channels of magnetic connection between the magnetosphere and foot points of the Sun's erupted flux rope; (c) cold CME ions observed with energized counter‐streaming electrons, evidence of CME plasma captured due to by reconnection between magnetic‐cloud and Alfvén‐wing field lines. The reported measurements advance our knowledge of CME interaction with planetary magnetospheres, and open new opportunities to understand how sub‐Alfvénic plasma flows impact astrophysical bodies such as Mercury, moons of Jupiter, and exoplanets close to their host stars.